Tinjauan Kriminologis Pelaku Pelecehan Seksual Terhadap Perempuan di Media Sosial (Instagram) Melalui Teori Aktivitas Rutin - Armina Wati; Untung Sumarwan (Universitas Budi Luhur, 2022)
This study discusses the causes of perpetrators having sex on social media (Instagram) and the impact caused by sexual victims on social media with reasons and various supporting factors, ranging from perpetrators who act, curiosity, opportunities, and lack of supervision. In this thesis research, routine activity theory is used. At this writing the researcher uses a qualitative approach method by digging information directly with the resource person and obtaining the necessary date and analyzing this problem using a descriptive method in group status research. The results of the study indicate that there are factors that cause the perpetrators to take these actions based on mere fun and curiosity, and are supported other factors, namely appropriate targets and lack of supervision from various parties, one of which is Instagram media.